Decreased Sulfamethoxazole Uptake in Lettuce (Lactuca sativa L.) due to Transpiration Inhibition by Polypropylene Microplastics - Li, Mei; Liu, Guanlin; Cai, Yimin; Guo, Ting; Xu, Yangyang; Zhao, Xinlin; Ji, Haibao; Ouyang, Da; Zhang, Haibo (Ecotoxicology and environmental safety, 2024)
Microplastics and antibiotics are emerging contaminants in agricultural soil that can have negative effects on crops. However, limited research has been conducted on the effects of the polypropylene (PP) microplastic and sulfamethoxazole (SMX) co-exposure on crops, specifically regarding the impact of PP microplastics on SMX uptake and transport in crops. In this study, hydroponic experiments were carried out using lettuce (Lactuca sativa L.), PP microplastics (1.0 g L−1), and SMX (0.5 mg L−1 or 2.5 mg L−1) to investigate the individual and co-exposure effects of PP microplastics and SMX on Lettuce growth, explore the uptake and translocation of SMX in lettuce and elucidate the underlying mechanism of PP microplastic impact on SMX uptake. Results demonstrated that co-exposure to 1.0 g L−1 of PP microplastics and 0.5 mg L−1 of SMX resulted in an enhanced toxic effect. However, no intensified toxic effect on the lettuce was observed when 1.0 g L−1 PP microplastics were added in the presence of 2.5 mg L−1 SMX, indicating that the SMX dominated the toxic effect on lettuce at high concentrations. Additionally, the study found that the water absorption process controlled by the aquaporin and transpiration contributed to the uptake and translocation of SMX in lettuce. When exposed to PP microplastics, no impact was observed on the aquaporin contents of the lettuce while the transpiration rate was significantly decreased by 31.6 % - 44.2 % resulting from microplastics adhered to the root surface. Therefore, in the presence of 2.5 mg L−1 SMX, the SMX uptake in the lettuce root was inhibited by 35.9 % (P < 0.05) when exposed to 1.0 g L−1 PP microplastic. This work deepens our understanding of the behaviour of microplastics and antibiotics in the terrestrial environment. [Display omitted] •Microplastic (MPs) sulfamethoxazole (SMX) showed a synergistic effect on the lettuce damage.•Transpiration and aquaporin are important SMX uptake pathways of lettuce.•MPs decreased SMX uptake via transpiration rather than aquaporin inhibition of lettuce.